Great Expectations for Lesbians to Provide Unpaid Care - Crewe, Carolina (Atlantis, 2008)
Lesbian unpaid caregivers face significant challenges in their caregiving because a seeming lack of additional family responsibilities constructs them as model caregivers, while they and their partners continue to experience homophobia and heterosexism. The intersection of female gender, lesbian sexual orientation and heteronormative public policies disadvantages lesbians financially, socially and in health related contexts.